Enhancement of stability of aqueous suspension of alumina nanoparticles by femtosecond laser irradiation - Seo, Youngsang; Choi, Tae-Youl; Ha, Jeonghong; Jeong, Dae-Yong; Lee, Seung Yong; Kim, Dongsik (AMER INST PHYSICS, 2015)
In this work, we report substantially enhanced colloidal stability of aqueous nanoparticle suspensions by ultrashort laser pulse irradiation. A Ti:Sapphire femtosecond laser (wavelength: 800 nm; pulse duration: 50 fs at full width at half maximum) was used to modify the electrochemical properties of nanoparticle suspensions at laser fluences below the particle ablation threshold. The colloidal stability of the suspension was evaluated by zeta potential and dynamic light scattering (DLS). The DLS results along with the images from transmission electron microscopy revealed that the laser irradiation caused no distinct morphological change to the individual alumina particles, but a substantial portion of the clustered particles was fragmented by the laser pulses, decreasing the apparent size of the suspended particles. Also, X-ray photoelectron spectroscopy analysis indicates that the laser irradiation modified the surface chemistry of the alumina particles. The stabilizing capability of the proposed technique was turned out to be better than that of conventional ultrasonic treatments. The stability of the laser-treated sample with no added surfactant was maintained for up to 30 days, without requiring an additional homogenizing process such as magnetic stirring. (C) 2015 AIP Publishing LLC.
Keywords: THERMAL-CONDUCTIVITY; CARBON NANOTUBES; PARTICLE-SIZE; NANOFLUIDS; AGGREGATION; DISPERSION; PROBE; WATER